Comparison of fisheries sectors of Japan and Turkey in production, consumption, trade and future possibilities - Guzel, Mahmut Munir; Kameda, Kazuhiko; Yamamoto, Naotoshi (Applied Studies in Agribusiness and Commerce, 2012)
The purpose of this study is to show some view-points such as the expansion of the mutual trade scale in fish and/or marine products, and newly effective use of edible marine bio-resources in each country. Total quantity of fisheries production, consumption (per capita), export and import quantity of Japan and Turkey based on 2010 were reported as 75.27 million tons, 653 thousand tons; 8.5 kg, 70.9 kg, 566 thousand tons, 55.1 thousand tons,; 473 thousand tons, 80, 7 thousand tons respectively. Turkey- Japan total amount of fisheries trade was more than 56 million US in 2011 and, but in 2000 was just over 14 million US . Japan and Turkey bilateral relations are friendly and cordial, and they are steadily improving. Therefore, they should prepare business plans or obtain funding for business plan development to identify new markets and explore business expansion opportunities.